Digital Plasmonic Absorption Modulator Exploiting Epsilon-Near-Zero in Transparent Conducting Oxides - U. Koch; C. Hoessbacher; J. Niegemann; C. Hafner; J. Leuthold (IEEE Photonics Journal, 2016)
Optical switches operated around $ε$ -near-zero (ENZ) of transparent conducting oxides (TCOs) are analyzed. A digital optical switching behavior is derived that is quite different from earlier predictions. The digital modulation characteristic originates from the fact that the nonlinear switching is, to a large extent, performed in the ENZ layer. The ENZ layer, however, arises from carrier accumulation in the TCO and is confined to a relatively thin layer with a characteristic dimension that does not change upon applying a higher voltage. An accurate treatment of this inhomogeneous layer is vital to reliably predict modulation characteristics. Such nonlinear accumulation processes and inhomogeneous material properties require refined simulations, which is why we apply an iterative solver based on a high-order finite-element method. More precisely, we solve the nonlinear stationary quantum hydrodynamic model to derive the carrier concentration upon applying an electrical field across the modulator. The result is then directly coupled to Maxwell's equation, which shows a strong local enhancement of the electromagnetic fields in the ENZ layer. In an exemplary implementation, we forecast the feasibility of 6 $μm $ long TCO absorption modulators with on-state losses of 2.8 dB and extinction ratios above 10 dB.